Does the ADMA/DDAH/NO pathway modulate early regression of left ventricular hypertrophy with esmolol?. (February 2016) - Quintana-Villamandos, Begoña; Delgado-Baeza, Emilio
Abstract: Hypertensive left ventricular hypertrophy (LVH) is a maladaptive response to chronic pressure overload and a strong independent risk factor for cardiovascular disease. Regression of LVH is associated with improved prognosis. Regression of LVH with antihypertensive therapy (angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, beta-blockers, calcium channel blockers, and diuretics) has been reported, although only after long-term treatment. Asymmetrical dimethylarginine (ADMA), the most potent endogenous NO synthase inhibitor, is emerging as an important cardiovascular risk factor in patients with arterial hypertension and LVH, and dimethylarginine dimethylaminohydrolase (DDAH) is the mechanism that most frequently leads to accumulation of ADMA (plasma ADMA is cleared in small part by renal excretion, although the bulk of ADMA is degraded by DDAH). Left ventricular mass is strongly modulated by the NO system. As an important inhibitor of the bioavailability of NO, ADMA is an underlying mechanism of LVH. Beta-blockers can induce regression of LVH and reduced plasma ADMA levels. Oxidative stress is increased in patients with LVH, and this in turn increases generation of ADMA. In a previous preclinical study of spontaneously hypertensive rats, we found that short-term treatment (48 h) with esmolol reverses early LVH, increases the bioavailability of NO, and improves antioxidant status in plasma. Therefore, we propose that the ADMA/DDAH/NO pathway could modulate early regression of LVH with esmolol.